2018
DOI: 10.1007/s13346-018-0543-3
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded self-nanomicellizing solid dispersion system: part I: development, optimization, characterization, and oral bioavailability

Abstract: Curcumin (CUR) is considered as one of the most bioactive molecules ever discovered from nature due to its proven anti-inflammatory and antioxidant in both preclinical and clinical studies. Despite its proven safety and efficacy, the clinical translation of CUR into a useful therapeutic agent is still limited due to its poor oral bioavailability. To overcome its limitation and enhance oral bioavailability by improving its aqueous solubility, stability, and intestinal permeability, a novel CUR formulation (NCF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…The solid dispersion formulation showed mean size of micelles in the range 721.4 to 1311.7 nm and PDI in range 0.409 to 1.612. Parikh et al [15] reported similar nanomicellizing formulations where the size of micelles was obtained as 63.05±5.24 nm with polydispersity index of 0.09±0.04. In these formulations they used Soluplus and Solutol HS-15 as polymers.…”
Section: Characterization Of Cu-sd For Self Micellizing Propertymentioning
confidence: 90%
See 1 more Smart Citation
“…The solid dispersion formulation showed mean size of micelles in the range 721.4 to 1311.7 nm and PDI in range 0.409 to 1.612. Parikh et al [15] reported similar nanomicellizing formulations where the size of micelles was obtained as 63.05±5.24 nm with polydispersity index of 0.09±0.04. In these formulations they used Soluplus and Solutol HS-15 as polymers.…”
Section: Characterization Of Cu-sd For Self Micellizing Propertymentioning
confidence: 90%
“…Nanomicellization is achieved with the help of amphiphilic carrier that can solubilize the drug in its hydrophobic core and also helps in improving the drug stability and solubility. Parika et al [15] Reported self nanomicellizing SD of Cu using soluplus as the carrier. However, the use of a high amount of polymer in the selfnanomicellizing SD may pose a problem in handling and dispensing of this formulation.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is complicated by the fact that crude curcumin contains a large fraction of insoluble curcumin that may not be accessible to the FGT epithelial tissues. We therefore also utilized 2 known polymers, PVP-K30 and Soluplus ® , to increase the solubility of crude curcumin by preparing solid dispersion formulations [29]. Groups of 4-6 mice received IVAG either PBS or 1 mg of crude curcumin in PBS or 100 µg curcumin in either solvent, 6 h before infection with a lethal dose of HSV-2.…”
Section: Ivag Pretreatment With Crude and Solubilized Curcumin Increamentioning
confidence: 99%
“…Furthermore, following oral and intraperitoneal (IP) delivery, nanocurcumin therapy can delay the progression of cataract development [26], protect against inflammatory markers and lipid metabolism in streptozotocin-induced diabetes, and have significant benefit in other disease models [27]. In addition, solid dispersion formulations of curcumin greatly increased its bioavailability and were shown to decrease cognitive impairment in an animal model of Alzheimer's disease [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Although active curcumin metabolites have many advantageous targets, they have low oral bioavailability due to their extensive first‐pass metabolism and poor aqueous solubility (Bayomi et al, ). Their poor chemical stability, permeability in vivo, aqueous solubility, and high first‐pass metabolism have been indicated as the potential factors contributing to its poor bioavailability overall (Parikh, Kathawala, Song, Zhou, & Garg, ). Thus, a series of synthetic modification, phosphatidylcholine formulations, lipid complexes, solid dispersions, prodrugs, microspheres, analogues, derivatives, and nanoscale formulations, to curcumin have been intensively studied in order to develop a molecule with enhanced bioactivities (Markatou et al, ; Paradkar, Ambike, Jadhav, & Mahadik, ; Sivasami & Hemalatha, ).…”
Section: The Chemical and Biological Nature Of Curcuminmentioning
confidence: 99%